A possible case of exfoliative dermatitis due to ibuprofen in an Eleven-month-old infant - Chatterjee, Sudipto; Vijendra, R.; H. T., Yashoda; Salian, Neil M. (International Journal of Basic & Clinical Pharmacology, 2018)
Ibuprofen is a NSAID belonging to the class of propionic acid derivatives which is widely used for its analgesic, antipyretic and anti-inflammatory action. Well-known adverse effects of ibuprofen include gastric irritability leading to nausea and vomiting as well as allergic manifestations such as urticaria and skin rashes. Severe ADRs include renal papillary necrosis, SJS/TEN, and thrombotic events leading to myocardial infarction and stroke. Authors present a case of exfoliative dermatitis in an 11-month-old infant possibly due to ibuprofen. An 11-month-old infant was prescribed syrup ibuprofen by a local medical practitioner for unclear reasons. Three days after ibuprofen therapy, the infant developed erythematous, crusting exfoliative lesions predominantly over the face with a few lesions over the lower abdomen. Subsequently, the infant was admitted to Kempegowda Institute of Medical Sciences and Research Center Hospital, Bangalore. A diagnosis of drug-induced exfoliative dermatitis was made after ruling out other causes. Treatment was initiated with intravenous and topical dexamethasone along with saline compressions and amoxicillin + clavulanic acid for secondary bacterial infection as well as topical emollient cream applied over the affected areas. The lesions improved significantly with the above management and the infant recovered enough to be discharged from the hospital after 3 days. The reaction was assessed to be “possible” as per Naranjo and WHO-UMC causality assessment scales, “moderately severe” on modified Hartwig’s severity assessment scale and “not preventable” according to Schumock and Thornton criteria. Severe and serious reactions such as exfoliative dermatitis can be caused by commonly used drugs like ibuprofen.